Plasma But Not Cerebrospinal Fluid Interleukin 7 and Interleukin 5 Levels Pre–Antiretroviral Therapy Commencement Predict Cryptococcosis-Associated Immune Reconstitution Inflammatory Syndrome. (5th July 2017) - Akilimali, Ngomu Akeem; Chang, Christina C; Muema, Daniel M; Reddy, Tarylee; Moosa, Mahomed-Yunus S; Lewin, Sharon R; French, Martyn A; Ndung'u, Thumbi
Abstract : High plasma IL-5 and IL-7 levels pre–antiretroviral therapy commencement predict cryptococcosis-associated immune reconstitution inflammatory syndrome (C-IRIS) in a case-control study of cryptocococcal meningitis. These data highlight the role of systemic IL-5/IL-7–related immune dysfunction in the pathogenesis of C-IRIS. Abstract: Background: Patients with human immunodeficiency virus/AIDS-associated cryptococcal meningitis (CM) frequently experience clinical deterioration, known as cryptococcosis-associated immune reconstitution inflammatory syndrome (C-IRIS), upon initiation of antiretroviral therapy (ART). The immunological mechanisms underlying C-IRIS are incompletely defined and no reliable predictive biomarkers exist. We investigated whether plasma or cerebrospinal fluid (CSF) levels of cytokines and chemokines predicted C-IRIS and are potential predictive biomarkers. Methods: Patients with CM who experienced C-IRIS (N = 27) upon ART initiation were compared to CD4 + T-cell count–matched patients without C-IRIS (N = 27). Plasma and CSF collected pre-ART were assayed for cytokines and chemokines using a 17-plex Luminex kit or enzyme-linked immunosorbent assay. Cox proportional hazards regression and principal component analyses were also performed. Results: Plasma interleukin (IL) 2, IL-4, IL-5, IL-7, IL-17, interferon-γ, and tumor necrosis factor-α levels were higher in C-IRIS patients compared to controls (all P < .05), with IL-5 and IL-7 significant after Bonferroni-Holm correction. In multivariate Cox proportional hazards regression, high IL-5 (hazard ratio [HR], 5.76 [95% confidence interval CI, .77–43.0]; P = .088) and IL-7 (HR, 9.30 [95% CI, 1.96–44.0]; P = .005) were predictive of C-IRIS. Plasma IL-5 ( P = .0008) and IL-10 ( P = .0089) were lower in those who achieved CSF cryptococcal culture negativity compared to those with positive cultures pre-ART. There were no significant differences in CSF cytokine or chemokine levels between cases and controls. Conclusions: High plasma IL-5 and IL-7 levels pre-ART were associated with increased risk of developing C-IRIS. High IL-5 levels may reflect a Th2 environment associated with impaired clearance of cryptococci while high IL-7 levels may reflect IL-7/IL-7R pathway dysfunction in T cells, both of which could be associated with C-IRIS immunopathogenesis.